The autograph book of visitors in Podhorce castle in the years 1923–1930 - Paduch, Katarzyna (Saeculum Christianum. Pismo Historyczne, 2021)
Podhorce is one of the greatest aristocratic residences. The owners of the palace were members of the families: Koniecpolscy, Sobiescy, Rzewuscy and Sanguszko. Waclaw Rzewu-ski (1709-1779) created in Podhorce a huge collection of works of art, he founded an armory, an archive and a library. Whereas Leon Rzewuski (1808-1869) gave museum character to the collection gathered in the palace. After visiting the residence the guests signed in the guest book of the palace. Based on the analysis of the guestbook from the years 1923-1930 it can be concluded that the palace was visited by representatives of different social strata. The largest group were the excursions organized by scholarly institutions (school children, scouts, students). The document includes signatures of the representatives of the polish gen-try, distinguished professors, scientists, researchers and senior clerics. The presented book contains about one thousand seven hundred autographs, that had been placed in the book for seven years of its conduct. A significant number of signatures in the document confirms the enormous interest in the Podhorce collection in the twentieth century.